Genomic landscape of metastatic lung adenocarcinomas from large-scale clinical sequencing - Dingbiao Li (Elsevier, 2021)
Background: Metastases are responsible for over 70% of deaths from lung adenocarcinomas. Previous large-scale studies of LUAD mainly focused on primary diseases. We aimed to comprehensively analyze the genomic landscape of metastatic LUADs and elucidate its clinical implications in the context of precision medicine.Methods: We performed retrospective analyses on targeted sequencing data of 3,743 primary tumors and 934 metastases from 4,480 patients with lung adenocarcinomas, and PD-L1 immunohistochemical data of 1,336 primary tumors and 252 metastases from 1,588 LUAD patients.Results: Metastases generally manifested significantly higher mutational burdens and chromosomal instability than primary lung adenocarcinomas. Clinically actionable alterations, including ALK mutations, ALK and ROS1 fusions, and MET copy number gains, were enriched in metastases, particularly metastases to some specific organs/tissues, such as lymph nodes, liver, and brain. PD-L1 expression decreased as the approximate metastatic distance increased. Additional data of paired primary tumors and metastases to lymph nodes and brain validated patterns of actionable alterations and candidates for metastatic drivers. Two evolutionary modes of metastatic dissemination, common origins and distinct origins, were identified in both types of primary-metastasis pairs.Conclusions: Our study showed heterogenous patterns of clinically actionable alterations, PD-L1 expressions, metastatic driver candidates, and evolutionary patterns among multiple types of metastases of lung adenocarcinomas, which may advise the planning of treatments and the identification of novel therapeutic targets.